The sands of Shark Island - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- School Ship Tobermory (Series)., 2017)
When twelve-year-old twins Ben and Fee MacTavish, along with their schoolmates, head to a small island in the Caribbean aboard the School Ship Tobermory, they learn extraordinary details about their captain's past and come face to face with modern-day pirates.